Nudge (Revised Edition) - Sunstein, Cass; Thaler, Richard (Ascent Audio, 2009)
Every day, we make decisions on topics ranging from personal investments to schools for our children to the meals we eat to the causes we champion. Unfortunately, we often choose poorly. The reason, the authors explain, is that, being human, we are all susceptible to various biases that can lead us to blunder. Our mistakes make us poorer and less healthy; we often make bad decisions involving education, personal finance, health care, mortgages and credit cards, the family, and even the planet itself. Thaler and Sunstein invite us to enter an alternative world, one that takes our humanness as a given. They show that by knowing how people think, we can design choice environments that make it easier for people to choose what is best for themselves, their families, and their society. Using colorful examples from the most important aspects of life, Thaler and Sunstein demonstrate how thoughtful "choice architecture" can be established to nudge us in beneficial directions without restricting freedom of choice. Nudge offers a unique new take-from neither the left nor the right-on many hot-button issues, for individuals and governments alike. This is one of the most engaging and provocative audio books to come along in many years. Included in this recording are a Bonus Chapter and a Postscript added in the Paperback Edition.
Online resource; Title from title page (viewed February 23, 2009)
Keywords: Economics -- Psychological aspects; Self-help; Consumer behaviour; Consumers' preferences; Health behavior; Medical policy -- Economic aspects; Consumer behavior; Decision making -- Psychological aspects; Choice (Psychology) -- Economic aspects; Économie politique; Aspect psychologique; Consommateurs; Préférences; Habitudes sanitaires; Politique sanitaire; Aspect économique; Consommateurs; Comportement; Prise de décision; Aspect psychologique; Choix (Psychologie); Aspect économique; Choice (Psychology); Economic aspects; Decision making; Psychological aspects; Economics; Psychological aspects; Medical policy; Economic aspects; Audiobooks